1998
DOI: 10.1042/bj3340147
|View full text |Cite
|
Sign up to set email alerts
|

Physiological concentration of amino acids regulates insulin-like-growth-factor-binding protein 1 expression

Abstract: Protein undernutrition is characterized by growth failure in young growing animals. Current evidence suggests that biosynthesis of insulin-like growth factor (IGF)-I and IGF-binding protein 1 (IGFBP-1) are key control points for nutritional regulation of growth. Here we examined the role of amino acid limitation in regulating the IGFBP-1 expression in the hepatic cell line. Our data show that leucine limitation strongly induces IGFBP-1 without affecting IGF-I and IGF-II expression in human HepG2 cells and in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 45 publications
6
44
0
Order By: Relevance
“…Direct, because EAAs stimulate the protein synthesis [31] and inhibit proteolysis at the same time [32]. Indirect, because EAAs boost protein formation by inducing protein production, and also increase the biological activity of insulin-like growth factor (IGF-I) [33]. The documented evidence that a three-month supplementation of 7.5 g/day of EAAs in older women increases base IGF-I expression [34] supports this hypothesis.…”
Section: A) Eaas and Physical Activitysupporting
confidence: 61%
“…Direct, because EAAs stimulate the protein synthesis [31] and inhibit proteolysis at the same time [32]. Indirect, because EAAs boost protein formation by inducing protein production, and also increase the biological activity of insulin-like growth factor (IGF-I) [33]. The documented evidence that a three-month supplementation of 7.5 g/day of EAAs in older women increases base IGF-I expression [34] supports this hypothesis.…”
Section: A) Eaas and Physical Activitysupporting
confidence: 61%
“…In recent years, evidence has accumulated that amino acids play an important role in controlling gene expression (30,32). Nevertheless, the molecular mechanisms involved in the amino acid regulation of mammalian gene expression have not been elucidated to date.…”
Section: Discussionmentioning
confidence: 99%
“…Straus (112) showed that single amino acid limitation of hepatoma cells in culture also resulted in an increase in IGFBP-1 mRNA. Jousse et al (57) investigated the expression of IGF-I, IGF-II, and IGFBP-1 in response to amino acid limitation in cultured cells and showed that IGFBP-1 mRNA and protein content was increased significantly, whereas the expression of the IGF-1 and IGF-II were either unaffected or slightly reduced. These observations appear to conflict with the observations of Entingh et al (26), who reported that the activation of the CHOP gene by amino acid deprivation of fibroblasts requires the presence of IGF-1.…”
Section: Insulin-like Growth Factor Binding Protein-1-mentioning
confidence: 99%